Diagnostic accuracy of MRI in the evaluation of adnexal masses using histopathology as the gold standard in a tertiary hospital of central Nepal - Prasad, V.Natraj (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Adnexal masses represent broad spectrum of gynecological conditions, ranging from benign cysts to malignant ovarian tumors. Accurate diagnosis and characterization are critical for clinical decision-making, including surgical planning, fertility preservation, and oncological referral. Magnetic Resonance Imaging (MRI), with superior soft-tissue contrast, multiplanar capability, and functional imaging techniques, offers improved characterization of adnexal masses. The objective of this study was to evaluate the diagnostic role of MRI in detecting and characterizing adnexal masses. Methods: A hospital-based prospective cross-sectional study was conducted among 80 female patients with adnexal masses identified on USG at the Department of Radiology, College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. This study was conducted between September 2024 to October, 2025. All patients went MRI evaluation followed by surgical excision and histopathological performance using (sensitivity, specificity, PPV and NPV) of MRI taking histopathology as gold standard. Data were entered and analyzed using SPSS-20. P-value<0.05 was considered as statistically significant. Results: The mean±SD of age was 38.42±6.28 years. Most patients (25%) were in 30-39 years with 62.5% premenopausal. Histopathology revealed 68.8% benign and 31.2% malignant lesions. MRI demonstrated sensitivity 85%, specificity 72%, PPV 78%, NPV 80%, and overall accuracy 77.5%. Restricted diffusion, solid components, peritoneal deposits, and contrast enhancement were significantly associated with the Adnexal masses (p < 0.05). Conclusion: MRI is reliable imaging modality for differentiating benign from malignant adnexal masses, identifying key imaging markers, and guiding clinical management. Integration of MRI into diagnostic pathways improves patient care and reduces unnecessary interventions.